Antitussive property and phytochamical characterization of Putat (Barringtonia racemosa) pulp extract. - Tanedo, June Mark Estante
Cough is one of the most common symptons for which patients seek medical attention (Digpinigaitis, 2011). The past two decades have seen a worldwide upsurge in the use of traditional medicine in both developed and developing countries (Jain, 2014). Putat (Barringtonia racemosa) fruits are popularly used as a folk medicine in Africa and Southeast Asia to treat cough (Orwa et al., 2009)., In the study, the ethanolic extract of Putat (Barringtonia racemosa) pulp was tested for its antitussive properties and phytochemical constituents. Probit analysis on the cytoxicity response of Putat pulp extract showed linear dose-response relationship on Artemia salina fingerlings with calculated LC50of222.75ug/mL. Using citric acid-induced cough in hamsters, the treatments having concentrations of 0.30 g extract/kg hamster and 0.50 g extract/kg hamster showed the most significant effect in reducing cough. Serial liquid-liquid extraction and phytochemical screening show that majority of the phytochemicals present in the extracts were saponins and flavonoids which were believed to have the highest contribution in the antitussive property of Putat pulp extract. Small amounts of polar compounds such as tannins, terpenes, phenolics and phytosterols were also found present in the extract. Studies on the structure elucidation and quantification of the phytochemicals of the Putat pulp are recommended. This information is necessary in the development of antitussives from Putat.